Zbornik povzetkov študentskih projektov / 8. letna konferenca mehatronike 2019, Maribor (University of Maribor Press, 2019)
Book of Abstracts, Student Projects / 8th Annual Conference of Mechatronics 2019. Faculty of Electrical Engineering and Computer Science (FERI) and Faculty of Mechanical Engineering (FS) of University of Maribor (UM) are the only ones in Slovenia to conduct quality independent study programmes of Mechatronics at the undergraduate academic, higher professional and at the postgraduate master level. The study programs of Mechatronics at the University of Maribor are distinguished by the project-oriented method of education, where students work in groups on various practical mechatronic problems. The results of their project work are presented at the end of the study year at the Mechatronics Annual Conference. Thus, this year, our students at the conference organized on June 27, 2019 represent a total of 42 projects. 12 projects will be represented by students of a professional study programme, 18 projects by students of an academic undergraduate study program, and 12 projects by students of the postgraduate master study programme. Summaries of these projects have been gathered in the present Proceedings where basic information is shown. More details you can find out at the conference. All of the projects are interesting and therefore we invite you on behalf of the FERI and FS organizers to take part in this year’s Annual Mechatronic Conference!